More than mere spectacle : coronations and inaugurations in the Habsburg monarchy during the eighteenth and nineteenth centuries - Gelder, Klaas van (Austrian and Habsburg studies ;, 2021)
"Across the medieval and early modern eras, new rulers were celebrated with increasingly elaborate coronations and inaugurations that symbolically conferred legitimacy and political power upon them. Many historians have considered rituals like these as irrelevant to understanding modern governance-an idea that this volume challenges through illuminating case studies focused on the eighteenth- and nineteenth-century Habsburg lands. Taking the formal elasticity of these events as the key to their lasting relevance, the contributors explore important questions around their political, legal, social, and cultural significance and their curious persistence as a historical phenomenon over time"--